"Modlitwa uboga" u Ojców Pustyni - Borkowska, Małgorzata (Vox Patrum, 1984)
The Desert Fathers seem to have led a singularly drab and dry life of prayer: those at least who are the real heroes of tha Gerontikon, the Old Men.